Proceedings of the 10th Hellenic Relativity Conference on recent developments in gravity : (World Scientific, 2003)
This book contains the proceedings of the 10th Hellenic Relativity Conference, held in Greece in 2002. It includes several plenary lectures given by leading experts on brane-world cosmology, radiative space–times, detection of gravitational waves, gamma-ray bursts and quantum gravity. There are a large number of contributed papers, organized into three broad subject areas: cosmology and brane gravity, mathematical relativity and astrophysical relativity, and the detection of gravitational waves.